Analisis Teknikal untuk Meramalkan Harga Saham Agribisnis pada Indeks D232 BEI - Rian Adi Prayoga; Septi Ambar Indraningtia Sukma; Purbowo Purbowo; Miftachul Chusnah (Program Studi Agribisnis, 2025)
This study analyzes the stock performance of selected agribusiness companies listed in the D232 Index on the Indonesia Stock Exchange from 2020 to 2024. The research aims to identify buy and sell signals using a combination of Moving Average (MA) and Stochastic Oscillator indicators. A quantitative descriptive method was employed, and eight representative stocks were analyzed. Results show that stocks such as AALI, ANDI, ANJT, and BISI exhibit strong buy signals supported by golden cross patterns and oversold conditions, while BWPT, CSRA, and DSNG present strong sell signals indicated by death cross patterns and overbought conditions. The integration of technical indicators allows investors to make informed decisions on entry and exit points. This study contributes to the literature by applying a dual-indicator approach specifically to the agribusiness sector, highlighting the relevance of MA and Stochastic Oscillator in predicting price trends and supporting investment strategies. Recommendations include using these indicators to guide trading decisions and continuously monitoring market movements for optimal timing.